The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/pace.13774
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous implantable cardioverter‐defibrillator in primary and secondary prevention of sudden cardiac death: A meta‐analysis

Abstract: Background Subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is gaining in popularity for primary and secondary prevention of sudden cardiac death. The objective was to evaluate the safety and clinical effectiveness of the S‐ICD for prevention of sudden cardiac death compared to transvenous cardioverter‐defibrillator (TV‐ICD). Methods A systematic review with meta‐analyses was performed. The electronic databases MEDLINE, EMBASE, SCI, and Cochrane Central Register of Controlled Trials were consulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…A meta‐analysis that included five case‐control studies demonstrated similar ICD infection rates for subcutaneous versus TV devices 20 . More recently, a meta‐analysis that included the same five case‐control studies and five additional series was published 21 and yielded similar results to the initial meta‐analysis. However, in a subsequent review 22 that included seven observational investigations that pooled data, the incidence rate ratio suggested that ICD infection was more prevalent in patients with subcutaneous versus TV‐ICD.…”
Section: S‐icd Infection Ratementioning
confidence: 74%
“…A meta‐analysis that included five case‐control studies demonstrated similar ICD infection rates for subcutaneous versus TV devices 20 . More recently, a meta‐analysis that included the same five case‐control studies and five additional series was published 21 and yielded similar results to the initial meta‐analysis. However, in a subsequent review 22 that included seven observational investigations that pooled data, the incidence rate ratio suggested that ICD infection was more prevalent in patients with subcutaneous versus TV‐ICD.…”
Section: S‐icd Infection Ratementioning
confidence: 74%
“…Although the reported studies questioned the appropriateness of ICD implantations in patients with CCI > 5 ( 39 , 40 ) or even > 4 ( 42 ), the high survival rates observed in our study cohort (in contrast to the predicted survival rates by the CCI score) suggest that it would have been arguable to withhold ICD implantation from these young but polymorbid patients. Another reason for the encouraging clinical performance could have been S-ICD implantation per se, as this technique reduces electrode movement, lead-related complications and procedural complications like pneumothorax therefore reducing morbidity in total ( 38 , 44 ). Consequently, our results might add value to the discussion about the guideline's class III indication for ICD-implantation in patients with a life expectancy of < 1 year ( 8 , 9 ), which is very often difficult to assess and define in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…S-ICDs are an alternative to TV-ICDs to avoid complications related to venous access, intracardiac leads, and infection. Pertaining to LMD, in a recent meta-analysis, S-ICDs had significantly less risk of lead-related complications and lead-related movement compared to TV-ICDs ( 7 ). Although its risk is lower, reel syndrome can alter the sensed vectors and result in inappropriate device shocks in S-ICD patients.…”
Section: Discussionmentioning
confidence: 99%